Roma 14:7-9 dan Konsep Kepemilikan Hidup: Relevansi bagi Penolakan Euthanasia dalam Etika Perjanjian Baru - Yenny Luisa Manongga; Cyntia Marlin; Arnold Tindas (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This article examines Romans 14:7-9 as a foundational biblical text for the concept of life ownership in New Testament ethics. Using a historical-exegetical and theological-systematic approach, it demonstrates that the passage clearly declares that neither life nor death belongs to the individual believer. Both are to be lived and died “to the Lord,” affirming that Christians are ultimately the possession of Christ as Kyrios. This theocentric view directly challenges the modern secular principle of radical patient autonomy that underpins euthanasia and physician-assisted suicide. The study provides a detailed exegesis of Romans 14:7-9 in its literary and historical context, explores parallel New Testament texts on life ownership, and discusses its ethical implications for contemporary medical practice. It argues that Romans 14:7-9 offers strong biblical grounds for rejecting active euthanasia while supporting compassionate palliative care that honors human dignity until natural death. In the Indonesian context, where euthanasia is legally prohibited, this perspective provides a robust theological foundation for Christian bioethics and public policy. A truly good death, according to the New Testament, is one that occurs in submission to the sovereignty of the risen Lord.